How to Preserve Liver Grafts From Circulatory Death With Long Warm Ischemia? A Retrospective Italian Cohort Study With Normothermic Regional Perfusion and Hypothermic Oxygenated Perfusion. Issue 11 (November 2021) - De Carlis, Riccardo; Schlegel, Andrea; Frassoni, Samuele; Olivieri, Tiziana; Ravaioli, Matteo; Camagni, Stefania; Patrono, Damiano; Bassi, Domenico; Pagano, Duilio; Di Sandro, Stefano; Lauterio, Andrea; Bagnardi, Vincenzo; et al.
Abstract : Background: Donation after circulatory death (DCD) in Italy, given its 20-min stand-off period, provides a unique bench test for normothermic regional perfusion (NRP) and dual hypothermic oxygenated machine perfusion (D-HOPE). Methods: We coordinated a multicenter retrospective Italian cohort study with 44 controlled DCD donors, who underwent NRP, to present transplant characteristics and results. To rank our results according to the high donor risk, we matched and compared a subgroup of 37 controlled DCD livers, preserved with NRP and D-HOPE, with static-preserved controlled DCD transplants from an established European program. Results: In the Italian cohort, D-HOPE was used in 84% of cases, and the primary nonfunction rate was 5%. Compared with the matched comparator group, the NRP + D-HOPE group showed a lower incidence of moderate and severe acute kidney injury (stage 2: 8% versus 27% and stage 3: 3% versus 27%; P  = 0.001). Ischemic cholangiopathy remained low (2-y proportion free: 97% versus 92%; P  = 0.317), despite the high-risk profile resulting from the longer donor warm ischemia in Italy (40 versus 18 min; P  < 0.001). Conclusions: These data suggest that NRP and D-HOPE yield good results in DCD livers with prolonged warm ischemia. Abstract : Supplemental Digital Content is available in the text.